Evaluasi Kegiatan Perawatan Kesehatan Keluarga Rawan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Background: Public Health Nursing (PHN) is one of Public Health Centre (PHC) programmes that has not been evaluated specigically. According to new paradigm of Public Health Centre, PHN activity has big contribution to achieve Kecamatan Sehat 2005 (suburban Health 2005). Many factors cause PHN programmes failed, some studies reported that PHC nurses/mid¬wifes did not really realized their role in promotive and preventive activity insteadof curative activity. The record and report systems also need investigation because the coverage has not been satisfying for years. The aim of this study is to eva luete the implementation of PHN programmes, including input, process, and output, specially risk-family and factors that influ¬ence the achievement of PHN activity in Mergangsan and Mantrijeron PHC in Yogyakarta, because those PHCs has the similarity in wide are but they very differ in the achievement although their region is very close. Method: This study was an evaluative study with case with cese study in Mergangsan and Mantrijeron PHC in Yogyakarta, using quantitaive methode. Data were analyzed descriptively. Data collection was done by interview and Discusion Focus Group with the head of PHC and nurses/midwifes of PHC, observation of the documents and interview with risk-family thad had ever got services form the PHC. Results and Discussion: The results showed that the number of nurses/midwifes in Mergangsan PHC was bigger than that in Mantrijeron PHC. The nurses/midwifes who had got training in Mergangsan was 47,05% and in Mantrijeron was 28,57%. Budgeting in Mantrijeron PHC was better those that in Mergangsan. In the proces of activity, Mantrijeron PHC mode a plan and their staff including the doctors. Were distributed evently in their area of coverage, Mergangsan PHC did not monitor: they thought that PHN was not the main activity, so they would do if they had time. So the outputs of those PHCs differd. Unfortunately in Mantrijeron PHC the proces of nursing serveces and documentation were not match the stabdard be¬cause of limiting time, money, and humen resources. Staffs thought that their main job was in out patients clinic (curative not promotive and preventive), the activity of nutrition, child and motherhood, TB prevention programme and diarchoe were not include in activity of PHN/risk family because the budgetting and recording/reporting systems were different. Summery: The coverage of those PHC were strongly influenced by style of leadership and the intensive of those PHC that were different. Perception of the staff of PHC toward PHN needed improvement by refreshing, many programmes in PHC caused the staffs confused.